2003
DOI: 10.1002/cncr.11073
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of vascular endothelial growth factor C and vascular endothelial growth factor receptor 3 in patients with nonsmall cell lung carcinoma

Abstract: A temperature‐sensitive polymer, poly(N‐isopropylacrylamide) [poly(NIPAM)], was tested to flocculate kaolinite clay suspensions. Settling tests at both room temperature and 40°C were carried out. The results show that settling at 40°C resulted in significantly higher settling rates and smaller sediment volumes. This behavior indicates that the polymer molecules changed from a stretched structure to a coil‐like conformation with increasing temperature. It is the change in conformation that induced more compacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
104
2
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 40 publications
10
104
2
4
Order By: Relevance
“…The present study also demonstrated that the survival of patients with stage I NSCLCs was significantly lower in patients with hypervascular tumours than in patients with hypovascular tumours. In addition, VEGF-C expression, another member of the VEGF family and reported to induce lymphangiogenesis (Skobe et al, 2001), was also associated with the prognosis of stage I patients, as reported previously (Kajita et al, 2001;Arinaga et al, 2003). Furthermore, previous clinical studies have shown that reduced expressions of several metastatic suppressor genes, including E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , are also associated with nodal metastases and a poor prognosis of patients with stage I NSCLCs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present study also demonstrated that the survival of patients with stage I NSCLCs was significantly lower in patients with hypervascular tumours than in patients with hypovascular tumours. In addition, VEGF-C expression, another member of the VEGF family and reported to induce lymphangiogenesis (Skobe et al, 2001), was also associated with the prognosis of stage I patients, as reported previously (Kajita et al, 2001;Arinaga et al, 2003). Furthermore, previous clinical studies have shown that reduced expressions of several metastatic suppressor genes, including E-cadherin (Sulzer et al, 1998;Liu et al, 2001), MRP-1/CD9, and KAI1/CD82 , are also associated with nodal metastases and a poor prognosis of patients with stage I NSCLCs.…”
Section: Discussionsupporting
confidence: 74%
“…Concerning TS expression, when the HSCORE of TS in a given specimen was X30, the sample was classified as TS-positive (Huang et al, 2000). Expressions of VEGF-A, VEGF-C, and E-cadherin were classified as follows: when X30% of the carcinoma cells in a given specimen were positively stained for VEGF-A, the sample was classified as VEGF-A-positive (Masuya et al, 2001); when X30% of the carcinoma cells in a given specimen were positively stained for VEGF-C, the sample was classified as VEGF-C-positive (Arinaga et al, 2003); and when X50% of the carcinoma cells in a given specimen were positively stained for E-cadherin, the sample was classified as E-cadherinpositive ).…”
Section: Assessment Of Immunohistochemical Stainingmentioning
confidence: 99%
“…41,42 Several reports have reported elevated levels of VEGFR-3 expression in tumors. 41,43,44 Nevertheless, a lack of correlation between density of a variety of lymphatic markers and lymphatic metastasis in cancer patients has also been reported. 45 The ELISA we report here should help to resolve these conflicting findings, especially as with the exception of a few studies using antibodies to detect VEGFR-3 by immunohistochemistry, most investigations used RT-PCR or Northern blot techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance-maintaining functions of the draining LN are thereby critically linked to the functionality of peripheral lymphatics, the pattern of drainage and inflammatory state of the tissue lymphatic vessels [1,115]. Expression of the lymphangiogenic factors VEGF-C and -D is significantly correlated with lymphangiogenesis (tumoral and nodal) and LN metastasis in a variety of primary tumors including thyroid, prostate, gastric, colorectal, lung and breast in both human and animal models [17,20,116,117]. Although VEGF-C is well-correlated with cancer metastasis, the requirement for tumor lymphangiogenesis is controversial, and there is evidence that VEGF-C can promote metastasis in the absence of tumor lymphangiogenesis [118][119][120][121][122][123].…”
Section: Chronic Graft Rejectionmentioning
confidence: 99%